The effect of customer loyalty and absorption capacity on business performance through risk management in Frozen Food MSMES - Fakhriana, Rizkia; Ajitya, Rizha; Fiola, Nike (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to examine the influence of customer loyalty and absorption capacity on business performance with risk management as a mediating variable in Frozen Food MSMEs in West Java Province. A quantitative approach with an explanatory design was used to test the causal relationship between variables, involving 401 respondents consisting of business owners, operational managers, and marketing managers. Data analysis was carried out using the Structural Equation Modeling (SEM) method through AMOS software version 26.0 to test the direct, indirect, and mediating influences. The results of the study show that customer loyalty and absorption capacity have a significant positive effect on risk management. In addition, these two variables also have an indirect influence on improving business performance through strengthening risk management practices. However, the direct influence of risk management on business performance is not significant, which suggests that its primary role is that of mediators. These findings expand theoretical insights by integrating the concepts of Resource-Based View (RBV), Dynamic Capability Theory (DCT), and Enterprise Risk Management (ERM). Practically, this study emphasizes the importance of increasing customer loyalty and knowledge absorption ability to strengthen the resilience and competitiveness of MSMEs in the frozen food sector.